Atmospheric Circulation Sensitivity to Changes in the Vertical Structure of Polar Warming. Issue 19 (30th September 2021) - Kim, Doyeon; Kang, Sarah M.; Merlis, Timothy M.; Shin, Yechul
Abstract: This study examines the effects of the vertical structure of polar warming on the remote atmospheric circulation. We apply thermal forcing at different vertical levels in the Northern Hemisphere polar region in two atmospheric global climate models of different complexity, both coupled to an aquaplanet slab ocean. The efficacy of polar heating in perturbing the remote climate increases with the altitude at which it is applied. This robust sensitivity arises from the dominance of surface temperature contribution to the outgoing longwave radiation owing to the large emissivity of the polar troposphere. An upper‐level polar heating has a smaller fraction of forcing balanced by radiative flux changes and a larger contribution from atmospheric energy transport changes, which provokes larger shifts in the extratropical jet and Hadley circulation. Our results suggest increasingly far‐reaching impacts of Arctic warming as a less surface‐trapped profile is projected for seasonally ice‐free conditions in the near future. Plain Language Summary: The amplified Arctic warming is a very prominent feature of global warming. The vertical structure of Arctic warming is determined by various mechanisms. For example, the ice‐albedo feedback gives rise to Arctic warming amplified near the surface, while atmospheric energy transport causes a pronounced mid‐tropospheric warming. This research addresses the question of how the remote effects of polar warming depend on its vertical structure. This study uses a series of experiments in which thermal forcing is applied at different vertical levels over the polar region. We find that the warming further from the surface is more effective at perturbing the remote climate, such as the extratropical jet and Hadley circulation, than the near‐surface warming. This suggests that Arctic warming may have more far‐reaching impacts in the near future as the Arctic transitions to an ice‐free summer season and there is less near‐surface warming. Key Points: An upper‐level warming in the Arctic is more efficient at perturbing remote large‐scale atmospheric circulations Near‐surface Arctic warming is effectively compensated by local outgoing longwave radiation rather than atmospheric energy transport Strong sensitivity of longwave at the surface is due to the large emissivity of the polar atmosphere